Preferences and Scores of Different Types of Exams during COVID-19 Pandemic in Faculty of Veterinary Medicine in Spain: A Cross-Sectional Study of Paper and E-exams - Pablo-Jesús Marín García; Alberto Arnau-Bonachera; Lola Llobat (MDPI AG, 2021)
The World Health Organization (WHO) officially declared the novel coronavirus (COVID-19) as a pandemic on 11 March 2020, and educational institutions have had to modify most of their activities (face-to-face activities were suspended). This situation forced academic institutions to modify the evaluation format of students. The use of proctoring systems quickly became widespread, although some controversies arose. The two main discussions regarding these systems are the integrity of the assessment and the capacity of the students to adapt to this new assessment method, without changes in theirs scores. To elucidate two controversies, we have analyzed the preferences and the scores obtained from a trial of 660 scores from 332 students of the third grade of Veterinary Medicine. The experiment involved three modalities of exam: an online format from home using the Respondus Lockdown Browser system (Modality 1), online in person using the Respondus Lockdown Browser system with the supervision of a teacher (Modality 2), or paper format in person with the supervision of a teacher (Modality 3). The results obtained showed that the students preferred Modality 1 (online at home with Respondus Lockdown Browser system). No statistical differences between the scores obtained by students were found between the three modalities analyzed. The proctoring system is a good method to adjudicate exams in higher education institutions, and the scores of students are similar to those obtained through traditional evaluation and control systems.